OPTIMIZATION OF PARAMETERS FOR LASER MARKING AND ENGRAVING ON PLYWOOD AND PINE WOOD MATERIALS - Gusts, Artis Stanislavs; Adijāns, Imants (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2021)
This publication shows the results of CO2 laser marking and engraving on plywood and pine materials at different speeds and powers. Plywood and pine materials were marked and engraved with four different speed and seven different power ratios. Marked and engraved line depth was measured for these materials. In this publication used SUNTOP CC-9060 CO2 laser machine and OLYMPUS OLS5000 laser microscope.